2018
DOI: 10.1029/2018wr023019
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Trajectories Associated With Solute Transport in a Heterogeneous Medium

Abstract: We present a trajectory‐based technique for calculating solute transport in a porous medium that has several advantages over existing methods. Unlike streamlines, the extended trajectories are influenced by each of the important parameters governing transport, including molecular diffusion and transverse dispersion. The approach is complete and does not require any additional techniques, such as operator splitting or particle tracking, in order to account for the full dispersion tensor. The semianalytic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 90 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…Many of these studies indicated that sandstones are characterized by subtle small‐scale heterogeneities that actively affect fluid flow. Variations in porosity and permeability affect the fluid velocity field, with high velocities being associated with regions of high porosity and permeability (Bloomfield et al, ; Grathwohl & Kleineidam, ; Vasco et al, ; Zahasky & Benson, ); and for multiphase fluid flow, variations in capillary pressure and relative permeability affect plume migration and residual saturation at both the pore and the field scale (Hingerl et al, ; Krevor et al, ; Krevor et al, ; Li & Benson, ; Perrin & Benson, ; Pini & Benson, ; Saadatpoor et al, ). In particular, Krevor et al () reported that regions presenting high capillary entry pressures (i.e., small pore throats) act as capillary barriers for the nonwetting fluid, leading to an increase in saturation of the latter in the preceding pores.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies indicated that sandstones are characterized by subtle small‐scale heterogeneities that actively affect fluid flow. Variations in porosity and permeability affect the fluid velocity field, with high velocities being associated with regions of high porosity and permeability (Bloomfield et al, ; Grathwohl & Kleineidam, ; Vasco et al, ; Zahasky & Benson, ); and for multiphase fluid flow, variations in capillary pressure and relative permeability affect plume migration and residual saturation at both the pore and the field scale (Hingerl et al, ; Krevor et al, ; Krevor et al, ; Li & Benson, ; Perrin & Benson, ; Pini & Benson, ; Saadatpoor et al, ). In particular, Krevor et al () reported that regions presenting high capillary entry pressures (i.e., small pore throats) act as capillary barriers for the nonwetting fluid, leading to an increase in saturation of the latter in the preceding pores.…”
Section: Introductionmentioning
confidence: 99%
“…This increasing end point pressure as the imbibition front approaches the end of the core is likely a combination of capillary heterogeneity and parameterization measurement error. Previous permeability inversion studies using this same core have indicated that the region near the outlet has a slightly lower permeability (Vasco et al, 2018), and therefore likely slightly higher capillary pressure. It is also important to note that capillary pressure end point is sensitive to water relative permeability, total imbibition rate, and water saturation measurement error.…”
Section: Discussionmentioning
confidence: 82%
“…The trajectory-mechanics approach described in and applied here is very general and can be used to model other hydrological processes such as tracer transport (Vasco et al, 2018a) and multiphase fluid flow. One advantage associated with transient pressure is the rapid propagation of a disturbance in comparison with the velocities associated with fluid transport.…”
Section: Discussionmentioning
confidence: 99%